Measuring the Level of Customer Satisfaction at Soekarno Hatta Airport Departure Terminal 3 - Budi Karyono, Aris; Simarmata, Juliater (Dinasti Publisher, 2024)
The article measuring the level of customer satisfaction at Soekarno Hatta Airport Departure Terminal 3 is a scientific literature review article within the scope of marketing management science. This article aims to create a hypothesis regarding the relationship between factors, which can then be used for further research in the field of human resource management. Descriptive qualitative research methodology was used in this research. The data used in this research comes from previous research which is still relevant to the current investigation. Data was collected from leading academic online platforms, including Publish or Perish, Google Scholar, digital reference books, and Sprott journals. The findings of this research are as follows: 1) The speed of check-in counter service influences customer satisfaction at Soekarno Hatta departure terminal 3; 2) Terminal 3 airport waiting room facilities influence customer satisfaction at Soekarno Hatta airport departure terminal 3; and 3) Customer complaint service influences customer satisfaction at Soekarno Hatta Departure Terminal 3.